Legal and technical challenges in the pursuit of cybercriminals: An analysis of the difficulties faced by the authorities (International Seven Journal of Multidisciplinary, 2023)
The rapid expansion of information and communication technology has shaped a continually growing digital landscape, wherein the internet and digital networks play a central role. However, this technological ubiquity has brought forth challenges, such as sophisticated and ever-evolving cybercrimes. This article addresses the complexity and diversity of cybercrimes, their legal implications, and the difficulties authorities face in identifying and prosecuting offenders. The research employs a qualitative approach, supported by literature review, to explore the nuances of preventing and combating these crimes. Gaps in specific legislation necessitate constant adaptation and updates within the legal system. Technologies such as digital forensic analysis, IP tracking, and cybersecurity have been utilized by both authorities and criminals. Collaboration and the continuous evolution of counter-strategies are vital to confronting this ever-changing reality in the digital age.